Digital adoption, self-efficacy, and business success – towards resilience and sustainability micro-entrepreneurs in the post-pandemic world - Mohd Arpi Arifin; Maheran Zakaria; Hasnun Anip Bustaman (Cogent Business & Management, 2023)
The prolonged lockdown inflicted by the COVID-19 pandemic has severely affected the sustainability of all economic sectors, including micro-entrepreneurs. In the endemic phase transition, many still struggle to survive. Anecdotal evidence showed that successful entrepreneurs are those who maximize digitalization and believe in their capabilities or self-efficacy. Intrigued with the evidence and emulating Social Cognitive Theory, this study investigates whether entrepreneurs with high digital adoption and self-efficacy will succeed in their business ventures. The study also examines the relationship between digital adoption and self-efficacy. Additionally, the study predicts that self-efficacy mediates the proposed relationship. Employing a quantitative and survey approach, the researchers distributed a questionnaire to 350 micro-entrepreneurs from marginalized communities in Kelantan, Malaysia. A total of 245 entrepreneurs responded, but only 240 data were usable. The SPSS and AMOS version 26 analysis indicated that; digital adoption and self-efficacy are significant determinants of micro-entrepreneurs' business success, digital adoption relates to self-efficacy, and self-efficacy significantly mediates the relationship between digital adoption and business success. The discoveries shed light on policymakers, poverty eradication agencies, academia, and the likes in formulating strategies and intervention programs to enhance marginalized entrepreneurs' success. Besides being resilient, successful entrepreneurs will elevate their social status and thus reduce national poverty. Eventually, the discoveries will fulfill the Sustainable Development Goals agenda of the United Nations in which all nations should be free from poverty by the year 2030.
Keywords: 650; business; digital adoption; micro-entrepreneurs; self-efficacy; success